Methodological Aspects and the Prognostic Value of Metabolic Tumor Volume assessed with 18F-FDG PET/CT in Lymphomas - Tutino, Francesca; Giovannini, Elisabetta; Pastorino, Sara; Ferrando, Ornella; Giovacchini, Giampiero; Ciarmiello, Andrea (Current Radiopharmaceuticals, 2022)
Although metabolic tumor volume (MTV) assessed with pretreatment 18F-FDG PET/CT has shown significant prognostic value across many lymphoma types, it is still not used in clinical practice due to technical concerns and the lack of standardisation. Numerous studies on the prognostic value of MTV in lymphomas have been published in recent years, but there is still no full agreement on the best methodology for MTV calculation. In this paper, we reviewed the methodological aspects of MTV assessment and reported recent works about its impact on outcome in lymphomas, with a focus on Hodgkin lymphoma (HL) and diffuse large B cell lymphoma (DLBCL).
Keywords: MTV